Spain transformed : the late Franco dictatorship, 1959 - 75 - Townson, Nigel Hrsg; Martín-Aceña, Pablo 1950- (Palgrave Macmillan, 2007)
The Golden Age of Spanish capitalism : economic growth without political freedom / Pablo Martín Aceña and Elena Martínez Ruiz -- Tourism and political change in Franco's Spain / Sasha D. Pack -- The change in mentalities during the late Franco Regime / Walter L. Bernecker -- How different was Spain? : the late Franco regime in Iiternational context / Tom Buchanan -- Order, progress, and syndicalism? : how the late Francoist authorities saw socio-economic change / Antonio Cazorla Sánchez -- New political mentalities in the tardofranquismo / Cristina Palomares -- Associations and the social origins of the transition during the late Franco regime / Pamela Radcliff -- Cultural diversity and the development of a pre-democratic civil society in Spain / Elisa Chul -- The Spanish church : change and continuity / William J. Callahan -- The origins of democratic support in post-Franco Spain : learning to be a democrat under authoritarian rule? / Mariano Torcal -- The United States and Spain : from Franco to Juan Carlos / Charles Powell-- The Franco dictatorship : a bifurcated regime? Edward Malefakis